Na rota do lixo: percursos de vida e trabalho dos catadores do Complexo de Triagem de Resíduos Sólidos do Jangurussu - Izaias, Fabiana Maria de Carvalho (2010)
This work intends to narrate, in an analytical way, the paths of life and work of garbage and recyclable material catchers from the sorting complex of solid dregs, operating in Jangurussu, Fortaleza, Ceará. It has been assumed that the collectors of garbage are people who act in the urban environment and that their work is characterized by informality when we talk about labor relations, and by precariousness in relation to their work conditions. The city is understood as a space of articulation of the capitalism way (mode) of production and is considered that the scavenger’s work, which is embedded in the productive chain of recycling, is guided by a rationality of organization of town from the logic of the capital. Based on this assumptions is that and through fragments of scavenger’s narrative who act in the complex of Jangurussu we reconstructed their migration routes, poverty and resistance against the established power control, crossing the stories of their lives with the biography of the city.